2010
DOI: 10.1093/hmg/ddq211
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of mouse congenital heart disease loci

Abstract: Empirical evidence supporting a genetic basis for the etiology of congenital heart disease (CHD) is limited and few disease-causing mutations have been identified. To identify novel CHD genes, we performed a forward genetic screen to identify mutant mouse lines with heritable CHD. Lines with recessive N-ethyl-N-nitrsourea-induced CHD-causing mutations were identified using a three-generation backcross. A hierarchical screening protocol was used to test the hypothesis that the fetal-to-neonatal circulatory tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…4a ). We then examined the Dync2h1 lln phenotype when combined with avc1 , a partial loss-of-function allele of Ift172 29 , 30 . While neural patterning in Ift172 avc1/avc1 mutants was nearly wild type ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4a ). We then examined the Dync2h1 lln phenotype when combined with avc1 , a partial loss-of-function allele of Ift172 29 , 30 . While neural patterning in Ift172 avc1/avc1 mutants was nearly wild type ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with identification of fetuses with CHD by ultrasound, we could exercise more caution in recovering stillborn pups, which otherwise might be cannibalized by the mother. We note another study screened for CHD mutants in a mouse mutagenesis screen with postnatal collection of stillborn pups and conducting phenotyping by histopathology 14 . While CHD mutants can be recovered in this manner, it is not high throughput and a significant fraction of the CHD mutants would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular and pulmonary defects often become evident after birth as a result of the transition from fetal to neonatal circulation (Kamp et al, 2010). A number of recent studies found epigenetic modifiers to be important in controlling cardiac maturation and differentiation (Conway et al, 2003;Chang and Bruneau, 2012).…”
Section: Rlf Mutants Display Defects In Cardiac Developmentmentioning
confidence: 99%